Analisis Investasi dan Pemilihan Portofolio Optimal pada Indeks Saham Kompas-100 dengan Menggunakan Single Index Model - Al Ayubi, Shalahudin; Asandimitra, Nadia (BISMA (Bisnis dan Manajemen), 2018)
Abstract A stock investment is one of alternatives that have a bright prospect in the futures. However, it is necessary to manage the risks, which is an important of choosing share intended. Up to now a relevan classic says œDont put all of your eggs in one basket. Therefore the share diversification is necessary as an investment choise to form a portfolio. The main purpose of this research are the ascertain the optimal portfolio by using single index model. Population to be chosen in the study is firms listed on Kompas-100. However, the simple included are only 33 firms that present continuously simultan on Kompas-100. This research results showed that there were ten stocks of portfolio candidates from thirty-three stocks researched with the cut-off-point (C*) of 0,016495. And ten of stocks which have the biggest excess return to beta (ERB) make up the optimal portfolio. Allocation of these funds comprises 1,1365% for Astra Agro Lestari Inc stock (AALI), 14,3439% for Astra International Inc stock (ASII), 5,072% for Cahroen Pokphand Indonesia Inc Stock (CPIN), 14,9259% for Gudang Garam Inc stock (GGRM), 10,1117% for Gajah Tunggal Inc stock (GJTL), 6,0152% for Indofood Sukses Makmur Inc stock (INDF), 7,7498% for Indocement Tunggal Perkasa Inc (INTP), 4,5907% for Kalbe Farma Inc stock (KLBF), 11,8773% for United Tractor Inc stock (UNTR), 24,177% for Unilever Indonesia Inc stock (UNVR). The portfolio rate of return of 3,62999% and risk of 9,45729%. The conclusion of this study is that rational investor will invest their funds in optimal portfolio comprises stocks candidates portfolio.